Pengaruh Media Pembelajaran Interaktif terhadap Peningkatan Hasil Belajar PJOK Siswa SD - Ratnawati (Jurnal Muara Olahraga, 2025)
Internal and external factors play a vital role in the learning process of students, especially in physical education. Internal factors include students’ attention, motivation, and curiosity, while external factors encompass available facilities, motivation from family and educators, and environmental conditions. The use of interactive learning media has significant potential to enhance student motivation and engagement, though challenges such as limited technological access and teacher readiness need to be addressed. This study reviews relevant literature to examine the influence of interactive media on elementary students’ learning processes and emphasizes the importance of developing learning models that integrate both internal and external factors to make learning more engaging and effective. The findings indicate that the success of learning heavily depends on these factors, and interactive media can serve as an important innovation in physical education to improve learning outcomes and students’ health.